Dialogues between feminism and social work in the 1980s and 1990s in Argentina (Papeles, 2025)
In this paper I summarize some of the results of my Master's thesis in Social Work at UNER called "Dialogues and intersections between feminism and social work in the 80s and 90s in Argentina.The objective is to explore the relationship between the field of Feminism and the profession/discipline of Social Work and focuses on the dialogical encounters and cross-debates between both fields in the Argentine context. The study covers the period from the late 1980s to the 1990s. The research aims to recover the history of these dialogues from the voices of social workers that we group into first and second generation.The development of the work is structured into 3 axes or topics: 1) The state of disciplinary debate about the links between feminism and social work. 2) The experiences and professional trajectories of first and second generation social workers and the dialogues with the feminisms of the 80s and 90s. 3) approaches to the process and the ways in which Feminisms were incorporated into Social Work courses in the Argentine context during the period.
Keywords: History; social work; Feminisms